Relationship of Blood Groups to the Incidence of Hyperuricemia and Hyperglycemia - Abbas Mehsen Gata; Sumayah Faruq Kasim; Sarah Mohssen Mohammed; Jaleel Samanje (Journal of Techniques)
Several experiments have been carried out to estimate the relationship between blood grouping types and the occurrence of diabetes, but not hyperuricemia. The effects of the potential correlation between the ABO blood groups and the incidence of these cases have been recorded in this study. The aim of this study is to see whether there is a connection between ABO blood groups and the occurrence of hyperuricemia and hyperglycemia among samples of Iraqi patients. This research was carried out in Educational Laboratories/Medical City (Baghdad Governorate). The research was carried out of the ABO blood with age range (40-70) years, ABO blood group was performed by the sliding method, while uric acid and glucose blood levels were measured by utilizing an enzymatic procedure.  There are significant differences in the levels of uric acid between blood groups (A and AB) and blood groups (A and O), while the levels of serum glucose were highly significant between blood groups (B and AB) and blood groups (AB and O). It is concluded that blood groups type AB could be the most vulnerable to the occurrence of hyperuricemia and hyperglycemia. However, further investigations with consideration to Rhesus factor Rh are required.